The morning show. Seasons 1 & 2 [videorecording (DVD)] - Carson, Jay, 1977- (Fifth Season, 2025)
Alex Levy's career is shaken after her co-anchor's scandal. As rising reporter Bradley Jackson challenges the status quo, both navigate fierce rivalries, shifting loyalties, and power struggles amid a turbulent newsroom and evolving media landscape.